What Happens When Employers Can No Longer Discriminate in Job Ads? - Peter J. Kuhn; Kailing Shen (Institute of Labor Economics (IZA), 2021)
When employers' explicit gender requests were unexpectedly removed from a Chinese job board overnight, pools of successful applicants became more integrated: women's (men's) share of call-backs to jobs that had requested men (women) rose by 63 (146) percent. The removal 'worked' in this sense because it generated a large increase in gender-mismatched applications, and because those applications were treated surprisingly well by employers. The removal had little or no effect on aggregate matching frictions. The job titles that were integrated however, were not the most gendered ones, and were disproportionately lower-wage jobs.
Keywords: J16; J63; J71; 330; gender; recruiting; job search; gender segregation; discrimination